2010
DOI: 10.1016/j.bpj.2010.06.054
|View full text |Cite
|
Sign up to set email alerts
|

SEIRA Spectroscopy on a Membrane Receptor Monolayer Using Lipoprotein Particles as Carriers

Abstract: Surface-enhanced infrared absorption (SEIRA) difference spectroscopy can probe reactions in a protein monolayer tethered to a nanostructured gold surface. SEIRA studies of membrane proteins, however, remain challenging due to sample stability, effects of the metal surface on function, and the need for a membrane-mimicking environment. Here we demonstrate and characterize a model system for membrane receptor investigations using SEIRA spectroscopy. The system employs nanoscale apolipoprotein bound bilayer (NABB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…More sophisticated methods are available for studying the biochemical properties of various membrane proteins by different analytical methods. 25,36,37,40,82,83 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More sophisticated methods are available for studying the biochemical properties of various membrane proteins by different analytical methods. 25,36,37,40,82,83 …”
Section: Discussionmentioning
confidence: 99%
“…, the disc diameter) has allowed researchers to isolate the monomeric and multimeric protein conformations for proteins such as bacteriorhodopsin. 3234 Lastly, these structures are being used in a wide variety of experimental settings that include NMR, 35 surface plasmon resonance, 36 as well as UV-visible, 29 infra-red 37 and fluorescence 28,38 spectroscopy. Nanodiscs thusly offer a versatile tool to deconstruct the factors that control the PR photocycle.…”
Section: Introductionmentioning
confidence: 99%
“…Protein immobilization based on His-tag technology is highly versatile. However, the binding strength of the His-tag to monovalent NTA is just moderate (K D in the order of 10 -5 -10 -6 M) [34].…”
Section: Surface-tethering Of Membrane Proteins With Protein Tagsmentioning
confidence: 99%
“…Cytochrome c was added to the solution and binding was monitored by SEIRAS for both CcO His-I and His-II. Although nanodiscs are a promising platform to study membrane proteins, only Vogel and coworkers reported a SEIRAS application up to now [34]. They incorporated the G-protein-coupled receptor (GPCR) rhodopsin into nanodisc particles.…”
Section: Orientational Control Of Surface-tethered Proteinsmentioning
confidence: 99%
“…Despite the confinement of the phospholipid bilayer by the MSP, NDs provide a native-like environment for membrane proteins which maintain their native structure and function 15 16 . Therefore, phospholipid NDs represent promising systems for the structural investigation of membrane proteins and their interaction with drug molecules by a variety of spectroscopic techniques including Raman scattering 17 and surface-enhanced infrared spectroscopy (SEIRS) 18 . Furthermore, NDs can also be used as building blocks for the self-assembly of larger hierarchical nanostructures.…”
mentioning
confidence: 99%